Ethyl trans-12-(pyridin-4-yl)-9,10-ethanoanthracene-11-carboxylate - Chandrasekar, S. (International Union of Crystallography, 2014)
In the title compound, C(24)H(21)NO(2), the residues at the central ethylene bridge are trans to each other. The dihedral angles between the pyridine and benzene rings are 67.09 (6) and 61.41 (5)°. In the crystal, centrosymmetrically related molecules are linked into dimers by pairs of C—H⋯O hydrogen bonds.